The practical skeptic : (McGraw-Hill Higher Education, 2006)
The Practical Skeptic is a concise introduction to sociology that focuses on core concepts as the central building blocks for understanding sociology. Lisa McIntyre's straightforward, lively, even humorous style and her emphasis on critical thinking make this an engaging and user-friendly text for students of all levels. Through this conversational style students are able to grasp key sociological concepts and learn the essential lesson that there is much that goes on in the social world that escapes the sociologically untrained eye.